A needs assessment for a “gender and disability in practice” programme in Lesotho - Mychalewicz, Edith (Organisational Psychology, 2022)
Background: This study focuses on a Gender and Disability programme. It is being implemented in Lesotho by an Austrian NGO, Diakonie ACT Austria, and the Basotho umbrella organisation of Disabled People's Organisations (DPO). All four DPOs in Lesotho are members of the umbrella body Lesotho National Federation of Organisations of the Disabled (LNFOD) and are supported through capacity building interventions by LNFOD and the Austrian NGO. Objectives: This evaluation explores the capacity building needs of LNFOD and its member DPOs. Moreover, this needs assessments sheds light on the extent to which the Gender and Disability programme is addressing the capacity building needs of LNFOD and the DPOs and the plausibility of the programme theory. Method: A generic qualitative inquiry approach was used as methodological framework. Different qualitative evaluative approaches influenced the research design such as the success case method and the fishbone root cause analysis to identify the performance needs of beneficiaries. Data collection approaches were a stakeholder workshop conducted with staff of Diakonie and LNFOD, and ten semi-structured interviews with staff of all four DPOs and LNFOD. Results: A root cause analysis of the performance needs of DPOs revealed the marginalisation of persons with disabilities (PwD) and DPOs in Lesotho. This was found to lead to a lack of tertiary education of staff and weak governance structures of DPOs. The performance needs of DPOs are “responsiveness to needs of PwD” and “to run their DPOs independently”. Conclusion: The low rate of tertiary education among PwD in Lesotho is an obstacle to establishing strong DPOs that can implement effective programmes independently. It is crucial to strengthen the leadership and M&E capacities of DPOs to assist them to grow and implement effective Gender and Disability programmes. I recommend strengthening the capacities of promising leaders at DPOs, employ a M&E Officer at LNFOD and consider a diverse team of PwD and persons without disabilities at the DPOs and at Diakonie.